2014
DOI: 10.1371/journal.pone.0096828
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Domain from S. cerevisiae Pat1 Displays Two Conserved Regions Involved in Decapping Factor Recruitment

Abstract: Eukaryotic mRNA decay is a highly regulated process allowing cells to rapidly modulate protein production in response to internal and environmental cues. Mature translatable eukaryotic mRNAs are protected from fast and uncontrolled degradation in the cytoplasm by two cis-acting stability determinants: a methylguanosine (m7G) cap and a poly(A) tail at their 5′ and 3′ extremities, respectively. The hydrolysis of the m7G cap structure, known as decapping, is performed by the complex composed of the Dcp2 catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…The Pat1C Domain Binds Dcp2 That Bridges Interaction with Edc3. We have previously shown using a yeast two-hybrid assay that the fungal-specific and conserved region located at the C-terminal part of Pat1C was important for interaction with Edc3 (21). Analysis of a deletion mutant demonstrated that the same region was required as well for growth at 37°C (21) revealing its functional importance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pat1C Domain Binds Dcp2 That Bridges Interaction with Edc3. We have previously shown using a yeast two-hybrid assay that the fungal-specific and conserved region located at the C-terminal part of Pat1C was important for interaction with Edc3 (21). Analysis of a deletion mutant demonstrated that the same region was required as well for growth at 37°C (21) revealing its functional importance.…”
Section: Resultsmentioning
confidence: 99%
“…This region displays a strongly conserved surface responsible for the direct interaction with Lsm2 and Lsm3 proteins from the Lsm1-7 complex, which binds to the 3′ end of oligoadenylated mRNAs (9,10,(18)(19)(20)(21). Pat1C is also important for Dcp2 and Xrn1 binding in yeast and human (8,17,22) as well as for yeast Edc3 (21) and human EDC4 recruitment (12). While the Dcp2, Xrn1, and EDC4 binding sites on Pat1C remain to be identified, the region responsible for yeast Edc3 binding has been mapped using the two-hybrid assay to a conserved region, which is only present at the C-terminal extremity of fungal Pat1 proteins (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, rps28aΔ and rps28bΔ strains could affect P-body assembly due to decreased levels of Rps28 protein. Indeed, Rps28 interacts with Edc3, Pat1, Lsm2/4/8 and Pby1 PB proteins as assessed by yeast two hybrid assays [36,37]. However, Rps28b protein reportedly only accounts for ~8% of the Rps28 protein population [20,38,39], and yet rps28bΔ strains exhibit a striking PB assembly defect, greater than that seen with rps28aΔ strains.…”
Section: Rps28 Protein Levels Do Not Account For Pb Assembly Defects mentioning
confidence: 99%
“…The disordered N-terminal region of Pat1 contains a conserved motif that interacts with the DEAD-box ATPase Dhh1, but is generally dispensable for cell growth and normal mRNA turnover (35, 36). The α-α superhelical C-terminal domain (PatC) interacts with Lsm1-7, which is required for bulk 5’-3’ mRNA degradation in vivo (27, 28, 3739). Removal of the unstructured middle domain severely attenuates decapping and 5’-3’ degradation, though the mechanism remains poorly understood (36, 40).…”
Section: Introductionmentioning
confidence: 99%